Peran Job Crafting Terhadap Kinerja Guru Pada Masa Pandemi Covid Melalui Burnout Dan work Life Balance - Dita Di Apriyanti; Rina Anindita; Dian Alfia Purwandari (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
ABSTRACT.This study aims to explore how the role of job crafting on teacher performance during the Covid pandemic through burnout and work life balance. The responden was 211 high school teachers in the West Java. Model Data collection using an online questionnaire with the method of Structural Equation Model (SEM) analysis. The results of this research show that job crafting has a positive effect on performance and work life balance while burnout has negative effect. Teacher performance is negatively affected by burnout and positively influenced by work life balance. Burnout and work life balance have been shown to partially mediate the relationship between job crafting and teacher performance, but the effect of job crafting on teacher performance is better directly without going through burnout and work life balance.